The “double being” of the human being: culture as the basis for becoming a personality - Illya Reyderman; Anastasiia Zinevych (Studia Philosophiae Christianae)
The main purpose of this article is to prove that one can become a personality only through culture. The authors propose to regard culture as a relatively autonomous spiritual sphere, which transcends the narrow requirements of the concrete society in its historical limitations. They argue that personality is the highest level of human development to emerge in culture, whereas the level of a biosocial organism is provided by society. The authors claim that only culture, be it religious or secular, contains an existential and spiritual imperative which demands each human being to realize one’s own potential humanity. They explain why in a postmodern world culture becomes an “existential choice” of each human being, depending on one’s free will: to inherit the culture, to become a human being of humanity or not. In the Free school of philosophy and culture seminars (Odesa, Ukraine), the authors propose to enter the field of culture through the mutual interpretation of a chosen masterpiece of world literature and to link its message with our lives.